2020
DOI: 10.3389/fneur.2020.00607
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of FES and SCS for Neuroplastic Recovery After SCI: Historical Perspectives and Future Directions

Abstract: There is increasing evidence that neuroplastic changes can occur even years after spinal cord injury, leading to reduced disability and better health which should reduce the cost of healthcare. In motor-incomplete spinal cord injury, recovery of leg function may occur if repetitive training causes afferent input to the lumbar spinal cord. The afferent input may be due to activity-based therapy without electrical stimulation but we present evidence that it is faster with electrical stimulation. This may be spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 130 publications
(195 reference statements)
0
18
0
Order By: Relevance
“…We believe that the muscle latency and amplitude adjustments observed in the current study may depend on a functional adaptation occurred in the spinal circuits during the training. An important prerequisite to implement this adaptation after SCI is to provide spinal cord with an appropriate quantity and quality of somato-sensory afferents [ 18 , 25 , 26 , 27 , 47 , 48 ]. Studies to date indicate that hybrid physical interventions, with natural movement assisted by mechanical or electrical muscle stimulation, are suitable paradigms to obtain consistent muscle and joint sensory receptors activations [ 18 , 25 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the muscle latency and amplitude adjustments observed in the current study may depend on a functional adaptation occurred in the spinal circuits during the training. An important prerequisite to implement this adaptation after SCI is to provide spinal cord with an appropriate quantity and quality of somato-sensory afferents [ 18 , 25 , 26 , 27 , 47 , 48 ]. Studies to date indicate that hybrid physical interventions, with natural movement assisted by mechanical or electrical muscle stimulation, are suitable paradigms to obtain consistent muscle and joint sensory receptors activations [ 18 , 25 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, on the basis of the well-documented association between spinal neuroplasticy and the amount of sensory afferents to the spinal cord [ 26 , 47 , 48 ], most of the neuronal adaptations should occur during the initial hemicycles of the pendulum test, as the amplitudes of the following leg oscillations were progressively reduced, producing an ever weakening sensory signal [ 51 ]. Therefore, the presence of the muscle responses mostly during the first flexion is a further clue indicating that the RF muscle behaviour observed in this study may be associated with a remodulation of spinal circuits.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that many clinicallycomplete lesions may nevertheless be anatomically incomplete, and that SCS can raise the excitability of spinal circuits to unmask weakened but surviving descending pathways (Minassian et al 2016). In conjunction with extensive rehabilitation, these pathways may be strengthened to further support restoration of function (Van Den Brand et al 2012, McPherson et al 2015, Krucoff et al 2016, Duffell and Donaldson 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode configuration (size, polarity, location) plays an important role in the electrical field produced by tSCS, and consequently the structures targeted. One of the criticisms of tSCS, when compared to the epidural alternative, is failure to create a localised electrical field thereby limiting activation selectivity [ 16 , 73 ]. This review found a lack of consensus regarding electrode configuration, particularly in the cervical region, and limited rationale for selected parameters throughout.…”
Section: Discussionmentioning
confidence: 99%